Percepción del servicio de atención al cliente en los establecimientos de alimentos y bebidas ubicados en el Malecón de Babahoyo - Palomeque Naranjo, Luis Junior (2021)
The perception of tourists is directly to the quality of the services that tourism service providers offer, as this in one way or the other has produced a betterment in the life quality of locals. In the same way, turning the region into a potential touristic destination not only for local tourism but for international tourists as well. The following project aims to determine the client service conditions offered by food and drinks establishments located by Babahoyo`s Malecon. The selected methodological tactic in this investigation was the “transversal method”, for which a survey was developed in order to question the tourist that visit food and drinks establishments by Babahoyo`s Malecon. the results allowed us to acknowledge that in these establishments located by Babahoyo`s Malecon exist several deficiencies, for which the service offered and the tourists` perception are considered a primary factor for the profitability of the sector.